Alessandro Buzo e o engajamento literário da periferia - Rejane Pivetta de Oliveira; Tiago Pellizaro (Estudos de Literatura Brasileira Contemporânea)
The currently literature produced by writers from the Brazilian suburbs forms a new way of thinking the representation of poverty, bringing up issues such as the author’s position and the role of literature as a tool of collective action with effects of mobilization and organization of the life of the marginalized and socially ex- cluded communities. The objective of this article is to discuss the topic of literary engagement as an inseparable component of peripheral literature, from the trajec- tory of Alessandro Buzo as a cultural agent, whose intervention gives to literature a function at the same time practical and symbolical.